Docência superior de conteúdos jurídicos: problemáticas e perspectivas para o século XXI - Silva, Maria Ivonete Santos (2015)
The choice of the theme \"Teaching legal content: problems and perspective for the twenty-first century\" was developed in the research that originated this thesis which is articulated with Knowledge Research and Educational Practices and the Group of Studies and Research in Developmental and Didactic Teacher Professionalization (GEPEDI), from the Post-graduate School of Education (FACED/UFU), by proposing the questioning of one of its main agents: the university teaching. In order to understand their practices, as from the teachers own education to their performance in the classroom, it is crucial to inter-relate it to the social agents that are mapping the guidelines and objectives in higher education teaching: the government departments (the Federal Constitution, the MEC, the INEP and CAPES), the class representative bodies (OAB and Abedi), university college department and the students whom all the process is or should aim at. This paper falls into the context of deadlocks and paradoxes, represented here as problems facing the legal and judicial teaching. It regards the choice to rethink Education and, especially, the Law in order to provide some answers to the so-called Legal content teaching crisis as from analyses of initiatives of institutions which implemented teacher development programs centered on the course itself, on students learning, on sharing of experience, on group support, on supervision and reflection. The methodology developed at all stages of the research, and which is based on the Diagnostic Study method, primarily followed a critical-reflexive perspective of analysis of data collected from the thorough exam of bibliographic and documental sources, the interpretation of results of a research conducted in the undergraduate degree in Law from Fadir, as well as, from observing forums held with the aim to restructure the Political Pedagogical Plan from college. Based on the diagnostic study carried out, it is concluded that the solution of the problems raised go beyond the strictu compliance with current legislation as well as the development of a Political Pedagogical Plan that, yet in practice, have not had the acceptance of teachers and, for this reason, it remains compromised the effectiveness of their proposals in the day by day university life. Therefore, and in view of the results achieved with the \"diagnostic study\" it has been found that only through a change in working conditions and in the attitude of those involved in the educational process before its commitment to educate the proposals aimed at improving education and, in particular, the content of legal education can be properly implemented.